Caring for late preterm infants: public health nurses' experiences - Genevieve Currie; Aliyah Dosani; Shahirose S. Premji; Sandra M. Reilly; Abhay K. Lodha; Marilyn Young (BMC, 2018)
Abstract Background Public health nurses (PHNs) care for and support late preterm infants (LPIs) and their families when they go home from the hospital. PHNs require evidence-informed guidelines to ensure appropriate and consistent care. The objective of this research study is to capture the lived experience of PHNs caring for LPIs in the community as a first step to improving the quality of care for LPIs and support for their parents. Methods To meet our objectives we chose a descriptive phenomenology approach as a method of inquiry. We conducted semi-structured interviews with PHNs (n = 10) to understand PHN perceptions of caring for LPIs and challenges in meeting the needs of families within the community. Interpretative thematic analysis revealed PHN perceptions of caring for LPIs and challenges in meeting the needs of families within the community. Results Four themes emerged from the data. First, PHNs expressed challenges with meeting the physiological needs of LPIs and gave voice to the resulting strain this causes for parents. Second, nurses conveyed that parents require more anticipatory guidance about the special demands associated with feeding LPIs. Third, PHNs relayed that parents sometimes receive inconsistent advice from different providers. Lastly, PHNs acknowledged that due to lack of resources, families sometimes did not receive the full scope of evidence informed care required by fragile, immature infants. Conclusion The care of LPIs by PHNs would benefit from more research about the needs of these infants and their families. Efforts to improve quality of care should focus on: evidence-informed guidelines, consistent care pathways, coordination of follow up care and financial resources, to provide physical, emotional, informational support that families require once they leave the hospital. More research on meeting the challenges of caring for LPIs and their families would provide direction for the competencies PHNs require to improve the quality of care in the community.